Supplementing Ca salts of soybean oil to late-gestating beef cows: impacts on performance and physiological responses of the offspring. (13th August 2020) - Brandão, Alice Poggi; Cooke, Reinaldo F; Schubach, Kelsey M; Rett, Bruna; Souza, Osvaldo A; Schachtschneider, Christopher L; Perry, George A; Arispe, Sergio A; Jump, Donald B; Pohler, Ky G; Bohnert, David W; Marques, Rodrigo S
Abstract: This experiment compared the performance and physiological responses of the offspring from cows supplemented with Ca salts of soybean oil (CSSO ) or prilled saturated fat (CON ) during late gestation. Nonlactating, pregnant, multiparous Angus × Hereford cows ( n = 104) that conceived during the same fixed-time artificial insemination protocol were assigned to this experiment. Cows were ranked by pregnancy sire (one of two sires), body weight (BW ), and body condition score (BCS ) on day −15 of the experiment (day 180 of gestation). Cows were then assigned to receive (dry matter basis) 415 g of soybean meal per cow daily in addition to: 1) 195 g/cow daily of CSSO ( n = 52) or 2) 170 g/cow daily of CON ( n = 52). Cows were maintained in two pastures (26 cows/treatment per pasture) and received daily 12.7 kg/cow (dry matter basis) of grass-alfalfa hay from day −15 to calving. Cows were segregated into 1 of 24 feeding pens three times weekly and received treatments individually from day 0 to calving. Calves were weaned on day 290 of the experiment, preconditioned for 35 d (day 291 to 325), and transferred to a feedyard, where they remained until slaughter (day 514). Cows receiving CSSO and their calves had greater ( P < 0.01) plasma concentrations of linoleic acid and total ω-6 PUFA compared with CON after calving. Concentrations of immunoglobulin G in the colostrum and in calf plasma 24 h after birth were greater ( P ≤ 0.02) in CSSO vs. CON cattle. Calves from CSSO cows had greater ( P ≤ 0.05) expression of adipogenic ( adipocyte fatty acid-binding protein and s tearoyl-CoA desaturase ) and myogenic ( myogenic differentiation 1 and myogenin ) genes in the longissimus muscle (LM ) compared with CON. No treatment differences in birth BW, weaning BW, and final preconditioning BW were noted ( P ≥ 0.36). Average daily gain and final BW in the feedyard were greater ( P ≤ 0.05) in steers from CSSO cows compared with CON. The incidence of calves diagnosed with BRD that required a second antimicrobial treatment was less ( P = 0.03) in calves from CSSO cows, resulting in reduced ( P = 0.05) need of treatments to regain health compared with CON. Upon slaughter, LM area was greater ( P = 0.03) in calves from CSSO cows compared with CON. Collectively, these results are indicative of programming effects on postnatal offspring growth and health resultant from CSSO supplementation to late-gestating cows. Hence, supplementing CSSO to beef cows during pregnancy might be a feasible alternative to optimize offspring productivity and welfare.